Revisiting agroecological transitions in Rwanda a decade later: the role of local knowledge in understanding the crop diversity–food security–land degradation nexus - Kuria, Anne W.; Pagella, Tim; Muthuri, Catherine W.; Sinclair, Fergus L. (Frontiers in Agronomy, 2025)
The challenge of achieving food security amidst broken food systems, the climate crisis, biodiversity loss, degrading land, and growing social inequity remains a critical development priority in alignment with the Vision 2030 agenda. While crop diversification is a cornerstone of agroecological transitions and food security, global food systems have often overlooked its potential, largely due to insufficient local participation and the reliance on blanket policies unsuitable for heterogeneous contexts. This article revisits agroecological transitions in Western Rwanda a decade after data collection, assessing the enduring relevance of local knowledge in understanding the crop diversity–food security–land degradation nexus. Using a systematic knowledge-based approach (AKT5), data were collected from 150 smallholder farmers through a Paired Catchment Assessment. Findings from the 1995–2015 period revealed a decline or disappearance of “low-value” crops, driven by the Crop Intensification Program (76%), land shortages (55%), and abandonment of slow-growing crops (49%). As a result, 83% of farmers reported food insecurity, primarily manifesting as seasonal food shortages (51%). Perennial crops emerged as critical for bridging hunger gaps, while reduced crop diversity forced many farmers to rely on off-farm food sources. The original analysis identified seven agroecological principles integral to the crop diversity–food security nexus: soil health, biodiversity, synergy, economic diversification, social values and diets, co-creation of knowledge, and participation. These findings varied significantly by land degradation status, emphasizing the importance of context-specific solutions. This study also showed that farmers have become more dependent on sourcing food off-farm, with food produced on-farm supporting farmers for an average of 6.6 months annually in 2015 compared to 10.1 months in 1995. This underpins the need to leverage ecological rather than administrative boundaries, ensuring connectivity within food systems, and fostering equitable trade mechanisms for smallholder farmers if agroecological transitions are to be realized. A decade later, the findings of this study were reflected upon and validated through recent literature, which underpins the validity of local knowledge in understanding of agroecological transitions. This advocates for stronger integration of local knowledge, stakeholder collaboration to promote the co-design of tailored context-appropriate, inclusive, and sustainable policy frameworks to foster sustainable food systems across scales.